SWOT Analysis: Strategies for Supporting the Economy of Kediri Post-Covid-19 Pandemic - Naning Fatmawatie (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
AbstractionThe success of economic development has indicators of economic factors and non-economic factors. The impact of the corona has made the Indonesian economy slump. The business world in various sectors, including trade, industry, and services, has also felt the impact of Covid 19. Various strategies have been carried out to maintain economic activity so that it continues to exist. The purpose of this study was to analyze the state of the city of Kediri after the covid 19 pandemic and to analyze the implementation of SWOT analysis to maintain the economy of the city of Kediri after the covid 19 pandemic. This type of research is qualitative descriptive. The results of this study indicate that the economic growth of the City of Kediri in 2021 has increased by 2.50%. The application of the Kediri City SWOT analyst in maintaining the economy after the COVID-19 pandemic is that the advantages include the cooperation between the city government and the cities/regencies of Blitar and Madiun, MSMEs, farmers, communities, zakat management institutions and banking institutions in the city of Kediri. The existence of a service city by carrying out digital acceleration comprehensively. The weakness is to avoid the gratification of cooperation with zakat management institutions to distribute donations. The decline in Gudang Garam cigarette sales. The stock of sugar and eggs in the city of Kediri is limited. Opportunities include the application of digitalization to MSMEs to increase sales turnover. Inflation is still at 1.9, but demand is still there. Inflation was successfully controlled, and as a result, many investors were interested in investing in the city of Kediri. Threats include an increase in open unemployment. In addition, there was also an increase in poverty to 7.69%